Learning abroad: Current status and prospects of cross-border mobility - Hübers, Berthold [Verfasser] (My University, 2013)
"In Germany there is a broad consensus among the partners involved regarding stays abroad during the individual's vocational training. Stays abroad are considered the ideal way to acquire the international occupational competence which is needed for many jobs today. Despite the importance attached to stays abroad, it had not how ever been known to date how many persons undergoing initial vocational training complete a phase of their learning in another country per year. A study conducted on behalf of the Education for Europe - National Agency (NA) at BIBB examined this question. The following article presents key findings from this study. It also examines what action would have to be taken so that the widelyaccepted practice of completing a phase of learning in a foreign country can be incorporated into the vocational education and training field as a normal, integrated learning segment." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.3.3 Mobilität; P 2.3 Auszubildende; Ausbildungsmobilität; Auszubildender; Auslandsaufenthalt; Mobilitätsbarriere; Mobilitätsforschung